ANALYSIS OF MULTICOMPONENT ADSORPTION VIA ORTHOGONAL PLACEMENT - Loyola C., Wilber (2001)
In this study we present the phenomenology of adsorption of a three component gaseous mixture on activated coal. The chosen gaseous mixture is constituted by nitrogen, ethane and propane, whlch are assumed to be in equllibrium at 298 K and a total pressure of 101 kPa. Solution of the resulting modal is analysed using the technique of orthogonal collocatlon which shows the advantage of being computatlonaliy straightforward to be implementad. Data for validating the modal were obtained from the literature(1,2,4) and the computational results are discussed.